P158 The outcome of colonic polyps with high grade dysplasia post endoscopic resection. (19th June 2022) - Eisa, Mohamed Gaafar; Wurm, Peter; Robinson, Richard
Abstract : Objectives: There are limited data on the risk of adenoma recurrence for polyps with high-grade dysplasia (HGD) that was removed at index colonoscopy. In a large observational study done in Taiwan, on the outcome of HGD polyp following endoscopic resection, the rates of metachronous adenoma and advanced adenoma at follow-up colonoscopies were 58% and 20%, respectively 1 . We examined the risk of adenoma recurrence for HGD post endoscopic resection in our bowel cancer-screening cohort. Methods: We carried out a retrospective observational study of polyps with HGD over a three-year period between 1 st January 2014 to 1 st January 2017. All polyps were removed from patients presenting under the NHS Bowel Cancer Screening Programme [BCSP]. Index and follow up [surveillance] procedures were reviewed via the national database [Exeter] and individual endoscopy reports [GI reporting tool- Unisoft]. We looked at patients' demographics, polyp size, morphology, and site. We excluded cases with metachronous colon cancer, patient lost to or with incomplete follow up and patients who were out of the BCS age at their follow up colonoscopy [over 75]. Results: 3, 162 BCS colonoscopies were carried out over a 3 year-period. 85 patients were found to have polyps with HGD at index colonoscopy, of which 21 patients were excluded for reasons described in below figure. Figure 1 Mean age was 66.7 years and mean follow-up period was 3.30 ± 0.93 [1-6] years after index colonoscopy. 40 patients [62.5%] were male and 24 [37.5%] female. 62 [96.9%] had described themselves, as white Caucasians and 2 patients were of non-white origin. The morphology of HGD polyps at index colonoscopy was as follows: 21 sessile, 29 pedunculated, 10 sub-pedunculated, 2 lateral spreading tumor- granular type [LST-G], one flat elevated [IIa] and one flat elevated with depressed center [IIa/c]. The mean size of HGD polyps was 21.9 mm [range 2-70 mm]. The total number of adenomatous polyps in patients with HGD at index colonoscopy was 244. 91.2% [n=59] of HGD polyps were found within the distal colon [splenic flexure to rectum] and 8.8% [n=5] were found proximally [caecum to transverse colon]. At subsequent follow up/surveillance colonoscopies 93 further adenomatous polyps were found. In contrast to index colonoscopy, 70.9% [n=66] of polyps were found proximally and 29.1% [n=27] were found distally. Most importantly, there was no recurrence of HGD polyp [at the site of original polyp] in term of metachronous adenoma or advanced adenoma [>1cm, HGD, >20% villous] on follow up colonoscopies. Conclusion: At this small cohort, although there was recurrence of colonic adenoma at follow up endoscopy, there was however, no recurrence of metachronous adenoma or advanced adenoma at the site of previous polypectomy for polyps with HGD. In addition, the risk of local recurrence following resection of polyps with HGD appeared to be low but the adenoma detection rate [ADR] in this patient group at follow up was high. Therefore, patients with HGD in index endoscopy warrant endoscopic follow up. Reference: Chang JJ, Chien CH et al. Long term outcomes of colon polyps with high grade dysplasia following endoscopic resection. BMC Gastroenterol. 2020 Nov 10;20(1):376. doi: 10.1186/s12876-020-01499-2. PMID: 33172387